2009
DOI: 10.1603/033.046.0524
|View full text |Cite
|
Sign up to set email alerts
|

Aedes triseriatusFemales Transovarially Infected With La Crosse Virus Mate More Efficiently Than Uninfected Mosquitoes

Abstract: The mating efficiencies of field-collected and laboratory-colonized Aedes triseriatus (Say) (Diptera: Culicidae) female mosquitoes transovarially-infected or uninfected with La Crosse virus (LACV) were compared. The females were placed in cages with age-matched males, and the insemination rates were determined daily by detection of sperm in the spermathecae. LACV-infected mosquitoes typically mated more quickly than uninfected mosquitoes. LACV load was not correlated with increased insemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Virus infection of insects by entomopathogenic and vectorborne viruses can cause both positive and negative effects on the development of the insect host (13,58). We found vitellogenin and actin (both within spot 374) to be upregulated in the TSWVexposed thrips.…”
Section: Discussionmentioning
confidence: 74%
“…Virus infection of insects by entomopathogenic and vectorborne viruses can cause both positive and negative effects on the development of the insect host (13,58). We found vitellogenin and actin (both within spot 374) to be upregulated in the TSWVexposed thrips.…”
Section: Discussionmentioning
confidence: 74%
“…Interactions of Ae. triseriatus with other mosquitoes have been speculated to result in competitive displacement, spill‐over effects, and enhanced LACV vectorial capacity (Bevins 2007, 2008, Reese et al 2009, Leisnham and Juliano 2012, Westby et al 2016). Additionally, laboratory‐based interspecific competition studies demonstrated that Ae.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rodent hosts do not exhibit overt illness (Borucki et al 2002). Furthermore, LACV can be transovarially transmitted from an infected female mosquito to her progeny, and recent studies have suggested that female mosquitoes infected with LACV mate more efficiently than uninfected mosquitoes (Reese et al 2009). Virus can be amplified substantially by this mechanism of transmission since each gonadotropic cycle leads to a multitude of infected progeny (Borucki et al 2002, Watts et al 1973).…”
Section: Bunyaviridaementioning
confidence: 99%